RESUMEN: A flexible class of multi-parameter qMRI protocols. (August 2021) - Monti, Serena; Pontillo, Giuseppe; Russo, Camilla; Cella, Laura; Cocozza, Sirio; Palma, Giuseppe
Highlights: A new class of multi-parameter quantitative MRI protocols is presented. The derived brain maps show high signal-to-noise ratio and accuracy. The RESUME N schemes can be easily integrated in research and routine protocols. Abstract: Purpose: To introduce a class of fast 3D quantitative MRI (qMRI) schemes (RESUME N, for N = 1, …, 4 ) that allow for a thorough characterization of microstructural properties of brain tissues. Methods: An arbitrary multi-echo GRE acquisition optimized for quantitative susceptibility mapping (QSM) is complemented with an appropriate low flip-angle GRE sequence drawn from four possible choices. The acquired signals are processed to analytically derive the longitudinal relaxation ( R 1 ) and free induction decay ( R 2 ∗ ) rates, as well as the proton density (PD) and QSM. A comprehensive modeling of the excitation and B 1 - profiles and of the RF-spoiling is included in the acquisition and processing pipeline. Results: The RESUME N maps appear homogeneous throughout the field-of-view and exhibit comparable values and high SNR across the considered range of N values. Conclusions: The introduced schemes represent a class of robust and flexible strategies to derive a thorough and fast qMRI study, suitable for a whole-brain acquisition with isotropic voxel resolution of 700 μ m in less than 15 min.